Advance care planning: the impact of Ceiling of Treatment plans in patients with Coordinate My Care. Issue 3 (22nd March 2018) - Broadhurst, Helen Lucy; Droney, Joanne; Callender, Tom; Shaw, Amanda; Riley, Julia
Abstract : Objectives: The aim of this evaluation is to describe the components and results of urgent care planning in Coordinate My Care (CMC), a digital clinical service for patients with life-limiting illness, for use if a patient is unable to make or express choices. Ceiling of treatment (CoT) plans were created detailing where the patient would like to receive their care and how aggressive medical interventions should be. Methods: A retrospective service evaluation was completed of all CMC records created between December 2015 and September 2016 (n=6854). CMC records were divided into two cohorts: those with a CoT plan and those without. The factors associated with these cohorts were reviewed including age, diagnosis, resuscitation status and preferences for place of death (PPD). Analysis of the non-mandatory free text section was carried out. Results: Two-thirds of patients had recorded decisions about CoT. Regardless of which CoT option was chosen, for most patients, PPD was home or care home. Patients with a CoT plan were more likely to have a documented resuscitation status. Patients with a CoT were more likely to die in their PPD (82%vs71%, OR 1.79, p<0.0001). A higher proportion of patients with a CoT decision died outside hospital. Conclusion: This analysis demonstrates that a substantial proportion of patients are willing to engage in urgent care planning. Three facets of urgent care planning identified include PPD, CoT and resuscitation status.